2003
DOI: 10.1089/109493103321167992
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Stereotype: The Case of Online Gaming

Abstract: Despite the rise of computer games as a leisure phenomenon, there has been relatively little research into this area. Furthermore, almost all of the research to date has concentrated on arcade or console games. More recently, the Internet has become a new medium in which players can play videogames. Since there is no published research in this area, some "benchmark" data on which future research can build was collected from two online gaming fan sites. Sociodemographics showed that the majority of players were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
275
4
19

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 369 publications
(330 citation statements)
references
References 10 publications
32
275
4
19
Order By: Relevance
“…Although various studies have investigated game players' stereotypical attributes (e.g., Griffiths, Davies, & Chappell, 2003;Kowert et al, 2013), few studies have looked at the attitudes of players themselves towards gaming stereotypes. Moreover, given that these studies mostly deploy a qualitative approach (e.g., Hayes, 2005;Royse et al, 2007), we are interested to provide a quantitative empirical account of internalized general and gender-specific gaming stereotypes by players.…”
mentioning
confidence: 99%
“…Although various studies have investigated game players' stereotypical attributes (e.g., Griffiths, Davies, & Chappell, 2003;Kowert et al, 2013), few studies have looked at the attitudes of players themselves towards gaming stereotypes. Moreover, given that these studies mostly deploy a qualitative approach (e.g., Hayes, 2005;Royse et al, 2007), we are interested to provide a quantitative empirical account of internalized general and gender-specific gaming stereotypes by players.…”
mentioning
confidence: 99%
“…Along with the new technology, the popularity of ICT-enabled gaming has raised attention [26,27,28]. In their literature review, Wattanasoontorn et al [27] analyzed health games and identified children, the elderly and patients with defined diseases as the most important target groups of serious games.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MMORPGs provide an immersive, dynamic and highly interactive computer gaming experience with a fully developed multiplayer universe (Griffiths, Davies & Chappell, 2003). Furthermore, socialisation in MMORPGs is an important aspect of game play and may provide stimulating experiences for gamers.…”
Section: Introductionmentioning
confidence: 99%